Anti-obesity Effect of Physalis Alkekengi in 3T3-L1 Cells through Inhibition of Adipogenesis and Activation of Lipolysis - Kim, Min Jeong; Nho, Chu Won (Sustainable Food System for a Healthy & Value-Oriented Life, 2023)
Physalin A (PA), the compound derived from Physalis alkekengi has been reported for various pharmacological properties including antioxidant, anti-inflammation activities. However, anti-obesity effect of Physalis alkekengi water extract (PAE) and PA has not been reported yet. In this study, we aimed to examine the anti-obesity effect of PAE and PA in 3T3-L1 cells. Cell viability assay was conducted using PAE and PA in 3T3-L1 cells and no significant cytotoxicity was observed below 160 μg/ml of PAE and 5 μM of PA. By treating PAE and PA, we measured the TG contents from cell supernatant media and observed a dose-dependent inhibition for lipid accumulation using TG assay and Oil red O staining. In addition, protein and mRNA expression of related key factors for adipogenesis and lipolysis were measured by western blotting and qRT-PCR in PAE and PA treated 3T3-L1 cells. Especially, PA decreased mRNA expression level of adipogenesis-related genes and regulated lipolysis-related genes in 3T3-L1 cells. These results suggest that PAE and its active compound, PA could be considered as potential candidates of nutraceuticals and natural medicine for prevention of obesity.